KEPENTINGAN INDONESIA DALAM KERJASAMA EKSPOR CRUDE PALM OIL (CPO) YANG BERKELANJUTAN DENGAN BELANDA - Mohd. Ali Akbar Velayati; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study will illustrate the economic and political interests of Indonesia in the export cooperation of CPO (Crude Palm Oil) with the Netherlands, especially from the signing of the Memorandum of Understanding (MoU) of Joint Production on Sustainable Palm Oil on September 29, 2019 in New York, United States.The method used in this research is qualitative research. Some of the data obtained came from books, journals, articles, annual reports, the internet and other media. In this study also used the perspective of liberalism, international cooperation theory, and national interest concept.This research shows that Indonesia always faces an increase in CPO exports to the Netherlands every year. Indonesia inserted economic and political interests in this MoU. Bilateral cooperation undertaken by Indonesia is mutually beneficial cooperation and has quite promising potential in long-term cooperation due to the dependency of the needs between the State of Indonesia and the Netherlands.  Keywords: National Interests, CPO, Exports, MoU.